2022
DOI: 10.1093/jamiaopen/ooac041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a machine learning approach utilizing wearable data for prediction of SARS-CoV-2 infection in healthcare workers

Abstract: Objective To determine whether a machine learning model can detect SARS-CoV-2 infection from physiological metrics collected from wearable devices. Materials and Methods Health care workers from seven hospitals were enrolled and prospectively followed in a multicenter observational study. Subjects downloaded a custom smart phone app and wore Apple Watches for the duration of the study period. Daily surveys related to symptoms… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The inter-rater agreement rate among the researchers in the full texts review was 97.67% (42/43). Therefore, 17 observational studies (total participants, N = 3628) [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], including a study from other sources [61], were included in this review (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The inter-rater agreement rate among the researchers in the full texts review was 97.67% (42/43). Therefore, 17 observational studies (total participants, N = 3628) [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], including a study from other sources [61], were included in this review (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…A total of four study types were analyzed, including four case-control studies [49,55,59,65], six retrospective analyses [54,[56][57][58]61,63], three crosssectional studies [51,52,60], and four prospective cohort studies [50,53,62,64]. Eleven studies [49,[51][52][53]55,[57][58][59]61,62,65] included SARS-CoV-2 negative individuals or healthy…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Weiting et al used several algorithms, including SVM, RF, and naive Bayes, to build an ML algorithm ensemble for the purpose of predicting the cardiovascular risk from wearable healthcare data-collection devices [ 107 ]. In a study involving 407 participants using smartwatches, a gradient-boosting algorithm identified and predicted SARS-CoV2 infections [ 108 ]. Researchers have used multiple-instance learning via an embedded instance selection (MILES) method for feature transformation to detect obstructive cardiomyopathy [ 109 ].…”
Section: Role Of Machine Learning In Diagnosticsmentioning
confidence: 99%